KREATIVITAS SISWA SMP N DITINJAU DARI TINGKAT PENDIDIKAN IBU - Tarnoto, Nissa; Purnamasari, Alfi (Universitas Ahmad Dahlan, 2009)
This research purpose was to test the difference of student creativity based on level of mother´s education. The subjects were students of SMPN especially the class 2E and the class 2F. The test was used were the Verbal Creativity Test and the Figural Creativity Test. The analysis of the data that was used in this research was t-test to reveal whether having the difference of student creativity based on level of mother´s education. Result of the analysis t-test was received by the value of 0.868 (p 0.05). This showed that there is no difference of student creativity based on level of mother education on student of SMPN.